Integritas dan Kepercayaan Bidan untuk Menciptakan Kemitraan dengan Dukun di Kota Mamuju - Nurgahayu Nurgahayu; Halida Thamrin (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
The position of midwives and traditional healers in partnership places midwives as birth attendants and changes the function of the traditional healers. In this case, the function of the traditional healers, which was originally used as the main helper in childbirth, has become a midwife partner whose function is to care for mothers and babies on a non-medical basis. The purpose of this study was to analyze the relationship between integrity and the trustworthiness of midwives in partnering with traditional healers in Mamuju City, West Sulawesi Province. This study used a cross-sectional approach. The population of this study was 99 village midwives, while the sample was 53 village midwives who were selected by accidental sampling technique. Integrity and trust were measured by filling out a questionnaire. Data analysis was carried out descriptively, followed by hypothesis testing using Fisher's exact test. The results of the analysis showed that integrity and trust research was at the "adequate" level. The p value was 0.02, so it was interpreted that there was a significant correlation in a positive direction. Furthermore, it was concluded that integrity was positively related to trust; the higher the integrity, the stronger the midwives' trust in partnering with traditional healers in Mamuju City.Keywords: integrity; trust; midwife; traditional healers; partners ABSTRAK Posisi bidan dan dukun dalam bermitra menempatkan bidan sebagai penolong persalinan dan merubah fungsi dukun. Dalam hal ini, fungsi dukun yang semula dijadikan sebagai penolong utama dalam persalinan menjadi mitra bidan yang berfungsi merawat ibu dan bayi pada segi non medis. Tujuan penelitian ini adalah untuk menganalisis hubungan antara integritas dengan kepercayaan bidan dalam bermitra dengan dukun di Kota Mamuju, Provinsi Sulawesi Barat. Penelitian ini menggunakan pendekatan cross-sectional. Populasi penelitian ini adalah 99 bidan desa,  sedangkan sampel adalah 53 bidan desa yang dipilih dengan teknik accidental sampling. Integritas dan kepercayaan diukur melalui pengisian kuesioner. Analisis data dilakukan secara deskriptif, dilanjutkan dengan pengujian hipotesis menggunakan Fisher’s exact test. Hasil analisis menunjukkan bahwa penelitian integritas dan kepercayaan berada dalam level “cukup”. Nilai p adalah 0,02, sehingga diinterpretasikan ada korelasi secara signifikan dengan arah positif. Selanjutnya disimpulkan bahwa integritas berhubungan secara positif kepercayaan; semakin tinggi integritas, maka semakin kuat kepercayaan bidan dalam bermitra dengan dukun di Kota Mamuju.Kata kunci: integritas; kepercayaan; bidan; dukun; mitra